MARKETPLACE CHINESE FOOD DENGAN SISTEM REKOMENDASI MENGGUNAKAN ITEM-BASED COLLABORATIVE FILTERING - Yanto, Yanto; Herwindiati, Dyah Erny; Lauro, Manatap Dolok (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Chinese food (typical Chinese cuisine) which is one of the most popular foods in the world. Almost all over the earth, there are always residing Chinese restaurants. Along with the development of culinary in Indonesia, Chinese food restaurant owners began to carry out certain specifications on the menus on offer. As customers will definitely be confused in the choice of food, when the Restaurants have more than one menu. Therefore we need a Marketplace with a recommendation system with the Item-based Collaborative Filtering method. Marketplace is an inter-organizational information system where buyers and sellers in the market communicate information about prices, products and are able to complete transactions via electronic communication channels. There are several stages in using this method, based on first assessing the data, then entering the calculation phase of the similarity between items and then calculating the prediction of item ratings for users.